A Light Purse Is a Heavy Curse: A Systematic Review - Suzie, Adee; Evan, Lau (De La Salle University, 2022)
The high level and rising cost in living standard conditions are affecting the individual’s and household’s savings behavior vividly in their day to day life. The general concern arises when individuals fail to address their retirement planning, problem that might affect the next generation. The need to boost financial knowledge and nurture savings behavior are essential to financial planning for retirement well-being. This current research establishes the understanding of how financial literacy influences savings habits for retirement well-being. Systematic review analysis was conducted, traced and implemented on academic databases from the period of 2006 to 2021. A total of 280 papers were identified while after exclusion protocol, 53 papers were included in the analysis and narrative synthesis was performed by the authors to consolidate the findings of the diverse studies. Findings reveal that financial literacy and savings behaviour are associated with retirement well-being, especially among working adults. In addition, family size, age, education, and geographical area were common components for both financial literacy and savings behavior literature. For retirement schemes, the contribution rates benefit package and government subsidies influenced the contributions from the individual. Moving forward, this research offers thoughts for interdisciplinary dimension as a provision for more resilience, equitable and sustainable need for retirement well-being research direction and development stream.